2020
DOI: 10.4236/ce.2020.118090
|View full text |Cite
|
Sign up to set email alerts
|

Acrostics and Crosswords as Advance Organizers to Meaningful Learning in Medical Education

Abstract: Education plays an essential role in human development. More than a simple process of just passing knowledge, is a dynamic social phenomenon. Thanks to it, the individual becomes more critical and understands better the reality that surrounds him. Consequently, the transformation is possibilited. Similarly, the strategies used to teach are fundamental to make better use of the teaching-learning process. Thus, this article aims to analyze the use of teaching methods in medical colleges associated with acrostics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 14 publications
0
3
0
1
Order By: Relevance
“…Previous studies have used films and characters (Hankir et al, 2015; as well as other entertainment activities, such as acrostics and crosswords (Monteiro et al, 2020), to enrich the educational experience. The validity and specificity of learning psychopathology through resources such as music, plays about depression and suicide (Souza et al, 2020a), poems, and online lectures have also been demonstrated.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have used films and characters (Hankir et al, 2015; as well as other entertainment activities, such as acrostics and crosswords (Monteiro et al, 2020), to enrich the educational experience. The validity and specificity of learning psychopathology through resources such as music, plays about depression and suicide (Souza et al, 2020a), poems, and online lectures have also been demonstrated.…”
Section: Discussionmentioning
confidence: 99%
“…This is why the method is known as meaningful learning: any new concept, idea or proposition will become more meaningful if the student can link it to preexisting knowledge. As a result, these anchors are also important for retrieving previously learned information (Agra et al, 2019;Monteiro et al, 2020).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Isso estimulou os alunos de todas as séries a resolverem a palavra cruzada. Os comentários acerca de cada palavra a ser resolvida Outras vantagens de se utilizar as palavras cruzadas como forma de avaliação é que este instrumento "pode ser adaptado para qualquer tema" (SILVA; SILVA-FORSBERG, 2009;FERREIRA, 2010;MONTEIRO et al, 2020) e sua confecção é uma atividade simples, principalmente quando ferramentas computacionais como programas são utilizadas corretamente para construção dos diagramas de cruzamento das palavras.…”
Section: O Uso De Palavras Cruzadas Como Forma De Avaliaçãounclassified